Efecto del aceite esencial de Schinus molle L “molle”, sobre Varroa destructor en colonias de Apis mellifera L. - Morillo Horna, María Azucena (2015)
This study aims to determine the effect of the essential oil of Schinus molle L "molle" on Varroa destructor in colonies of Apis mellifera L., for which nine hives of native bees colonies located in the Ex-CEPCAM was used National University of Trujillo, which were divided into 3 groups of 3 hives randomly (A, B, C) these groups were fed with 500mL of sugar syrup concentrations T1 = 0mL , T2 = 1.0 mL, 1.5 mL and T3 = T4 = 2.0ml essential oil of Schinus molle respectively. For the assessment of mortality fall trap she was laid for two days on the floor of each hive and then count the number of dead mites fallen into the trap after consumption of whole syrup. For statistical analysis of mortality ANOVA and mean comparison with the Tuckey test with 95% confidence were applied statistically significant differences were found by applying different treatments except to compare treatments T3 and T2 ; regarding the effectiveness of essential oil of Schinus molle concentration of 1.0 ml / L was 72.2%; in the concentration of 1.5 ml / L of 80% and the concentration of 2.0 ml / L of 89% the latter more so it can be considered as an alternative to the integrated management of Varroa destructor in hives of native bees being . Keywords: Varroa destructor L, Schinus molle L., essential oil, acaricide, Apis mellifera.